2019
DOI: 10.5455/sf.51921
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal Exploration in Nigeria

Abstract: The geological structure of Nigeria influences geothermal exploration extent within each geological province. Sedimentary basins in Nigeria have been explored for hydrocarbons for several decades, thus the oil companies collected large subsurface temperature data basis. But not much is known about geothermal conditions within Nigerian Precambrian crystalline province.On the basis of BHT data from oil wells it has been found that geothermal gradient in Niger Delta ranges from 1.3 to 4.7°C/100m and in Anambra Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…It is interesting to observe that volcanism in the region is inseparable from the anticlinal folds. In the region, a hot spring (i.e., middle Benue spring) with the highest temperature of around 53.5 °C was recorded [67] .…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to observe that volcanism in the region is inseparable from the anticlinal folds. In the region, a hot spring (i.e., middle Benue spring) with the highest temperature of around 53.5 °C was recorded [67] .…”
Section: Resultsmentioning
confidence: 99%
“…The average aeromagnetic data interpretation revealed that the geothermal gradient from the Chad Basin varied from 3.00 to 6.44 °C/100 m, the thermal conductivity varied from 0.58 to 4.21 WmK -1 , while the heat flow ranged from 45 to 90 mWm -2 , respectively (Kwaya et al 2016). Meanwhile, the gravity data interpretation showed that the geothermal reservoirs in the Chad Basin are housed within the depth varying from 23 to 26 km (Kwaya and Kurowska, 2018). The geothermal anomalies in the basin are as a result of the thinned crust resting above the fault-confined graben and horst networks from the tectonic activities.…”
Section: Geothermal Energy Exploration: Case Historiesmentioning
confidence: 97%
“…The spring flows from an approximate depth of 700 m below the earth surface. It is believed to be the only juvenile water in Nigeria (Garba et al 2012) (Kwaya and Kurowska 2018). The identified geothermal reservoirs will boost the Nigerian energy mix if the government and other concerned agencies could look into the installation of geothermal binary power generation system for the production of electricity, since there is no active volcanic domain in Nigeria that could be adopted for other applications of geothermal energy other than electricity.…”
Section: Geothermal Energy Exploration: Case Historiesmentioning
confidence: 99%